2018
DOI: 10.1097/wnr.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 protection against Aβ1–42-induced hippocampal neuronal inflammation and apoptosis by TβR-I

Abstract: Alzheimer's disease (AD), the most common chronic neurodegenerative disease, is pathologically characterized by the formation of neurofibrillary tangles because of hyperphosphorylation of tau protein and extracellular deposits of amyloid-β (Aβ) protein termed senile plaques. Recent studies indicate that neuronal apoptosis caused by chronic neuroinflammation is one of the important pathogenesis of AD. Transforming growth factor (TGF)-β1 is a pleiotropic cytokine with immunosuppressive and anti-inflammatory prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…Importantly, TGF-β1 administration in microglial cultures inhibited all the above changes caused by 3-AP, which provide a direct evidence for TGF-β1 inhibitory modulation in 3-AP-induced microglial activation. In line with this, the research results from our and other laboratories support the viewpoint that microglial activity in vitro can be suppressed by TGF-β1 via decreasing inflammatory mediator (such as TNF-α, IL-1β, NO and ROS) or increasing neurotrophic factor (IGF-1, GDNF, and BDNF) productions induced by LPS, MPP + or Aβ 1−42 (Herrera-Molina and von Bernhardi, 2005;Ramírez et al, 2005;Spittau et al, 2013;Liu et al, 2016;Chen et al, 2017;Fang et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Importantly, TGF-β1 administration in microglial cultures inhibited all the above changes caused by 3-AP, which provide a direct evidence for TGF-β1 inhibitory modulation in 3-AP-induced microglial activation. In line with this, the research results from our and other laboratories support the viewpoint that microglial activity in vitro can be suppressed by TGF-β1 via decreasing inflammatory mediator (such as TNF-α, IL-1β, NO and ROS) or increasing neurotrophic factor (IGF-1, GDNF, and BDNF) productions induced by LPS, MPP + or Aβ 1−42 (Herrera-Molina and von Bernhardi, 2005;Ramírez et al, 2005;Spittau et al, 2013;Liu et al, 2016;Chen et al, 2017;Fang et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…express little if any TGF-β1 less in normal states (da Cunha et al, 1993;Ata et al, 1997;Vivien et al, 1998;De Groot et al, 1999;de Sampaioe Spohr et al, 2002), but throughout the CNS, the isoforms of TGF-β and TGF-β receptors have been found in all glial cells, including astrocytes and microglia (Vivien et al, 1998;Vivien and Ali, 2006). Recently, several lines of evidence from our laboratory have shown that TGF-β1 exerts neuroprotective role in neurodegenerative diseases by inhibiting microglia-mediated neuroinflammation (Shen et al, 2014;Chen et al, , 2017Liu et al, 2016;Fang et al, 2018), but its role in CA has still not been elucidated. In the present study, apart from generating destruction to neurons, 3-AP induced an excessive activation of microglial cells as determined by morphological alteration, the upregulated CD11b expression and percentage of CD40 + and CD86 + microglial cells, as well as the enhanced inflammatory responses manifested as the increased mRNA and protein level of the pro-inflammatory mediators (TNF-α and IL-1β) and decreased level of the neurotrophic factor IGF-1 in both the brain stem and the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our previous studies showed that microglia and astrocytes that were damaged by β-amyloid peptide [25][26][27][28][29][30][31][32][33][34][35] could release inflammatory factors such as interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor (TNF-α) (Ma, Ding et al, 2015;Zhou et al, 2014). These results suggest that the release of inflammatory cytokines in neurons and astrocytes is closely associated with the level of Aβ and eventually leads to the development of AD (Fang, Sun, Zhou, Qiu, & Peng, 2018).…”
mentioning
confidence: 99%
“…The disease manifests as impaired cognitive function caused by neuronal necrosis in specific brain regions(Hyman, Van Hoesen, Damasio, & Barnes, 1984), and eventually leads to death due to brain dysfunction(Pagani et al, 2017). Although the exact pathology is still debated, it is hypothesized that the continuous neuron loss and brain structure dystrophy is induced by the accumulation of Amyloid ß (A ß) protein and cell inflammation(Fang, Sun, Zhou, Qiu, & Peng, 2018), which leads to memory loss and cognitive decline. Appropriate treatment during disease progression could help slow down the disease and it is therefore important to understand the biological and physiological changes that occur during the course of the disease.…”
Section: Introductionmentioning
confidence: 99%